The Influence of Promotion, Service Quality, Price, and Store Atmosphere on Purchasing Decisions - Nurlia Fauza; Wiku Suryomurti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The study aims to find out the impact of promotions, quality of service, price, and store atmosphere on purchasing decisions at Amor Cakes & Bakery of Islamic university students in Bogor. This type of research is explanatory research that explains or proves the relationship between variables through the testing of hypotheses. The sample technique used purposive sampling with a total of 109 respondents. The selected respondents were students of IAI Tazkia who had purchased Amor Cakes & Bakery products. The research used double linear regression analysis using SPSS ver. 20 and Eviews ver. 12. The results of this study show that (1) promotion has a positive and significant impact on the purchase decision, (2) service quality has a positive impact and significant effect on the purchasing decision; (3) price positively and significantly influences on the purchase decisions, (4) store atmosphere variable have a negative and significant influence on the decision of purchase of Amor Cakes & Bakery. (5) promotion variables, quality of service, price, and quality of services simultaneously have a significant and positive impact on purchasing decisions.